2014
DOI: 10.1523/jneurosci.3898-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Jak/Stat Signaling Stimulates Zebrafish Optic Nerve Regeneration and Overcomes the Inhibitory Actions of Socs3 and Sfpq

Abstract: The regenerative failure of mammalian optic axons is partly mediated by Socs3-dependent inhibition of Jak/Stat signaling (Smith et al., 2009(Smith et al., , 2011. Whether Jak/Stat signaling is part of the normal regenerative response observed in animals that exhibit an intrinsic capacity for optic nerve regeneration, such as zebrafish, remains unknown. Nor is it known whether the repression of regenerative inhibitors, such as Socs3, contributes to the robust regenerative response of zebrafish to optic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 49 publications
3
95
0
1
Order By: Relevance
“…It has been reported that the IL-6 family stimulates Jak/STAT3 signaling in the eye (3537). Also, high glucose can stimulate STAT3 phosphorylation in retinal endothelial and RPE cells (3840).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the IL-6 family stimulates Jak/STAT3 signaling in the eye (3537). Also, high glucose can stimulate STAT3 phosphorylation in retinal endothelial and RPE cells (3840).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were pretreated with PDTC and then stimulated with LPS. As shown in Resveratrol inhibits the LPS-induced activation of the JAK/STAT pathway STAT1 and STAT3 are important transcription factors in the immune response, and also play roles in the inflammatory signaling cascades triggered by LPS, interferon-gamma, and other cytokines [19,20]. Therefore, we investigated whether the anti-inflammatory effects of resveratrol on the expression of HMGB1 and IL-6 were exerted by inhibiting the JAK/STAT signaling pathway.…”
Section: Resveratrol Inhibits Nf-κb Activation and Iκbα Phosphorylationmentioning
confidence: 98%
“…Secondly, involvement in neural repair mechanisms was suggested by the observation that CLCF1, CRLF1, CNTFR, leukaemia inhibitory factor, LIFR, IL-11 and IL-11 receptor mRNA levels are all elevated after optic nerve lesion in zebrafish [44] and sciatic nerve injury in mice [45]. Indeed, knockdown of either CLCF1 or CRLF1 genes in zebrafish retinal explants suppressed optic axon regrowth [44] suggesting CLCF1/CRLF1 may enhance optic nerve regeneration in mammals.…”
Section: Effects Of Clcf1 and Crlf1 Composite Cytokines On The Neuralmentioning
confidence: 99%